Compton Wynyates
The High table of the hall was lighted by a bay window in much the same manner used at the Hampton Court. The table and furniture, with the exception of the clock, are of the period. The table, with its 23-foot-long, 3-inch thick top, was made from an elm plank and is the original. It was still usual for the master of the house to sit with the whole household at mealtime. Rushes would be lain on the stone floor, and in winter, the central wood fire warmed the whole space. On feast days, or when the king and his court graced the hall, there would be music from the gallery above, and later, after the meal, the ladies could watch the entertainment from above.